2018
DOI: 10.3389/fimmu.2018.02282
|View full text |Cite
|
Sign up to set email alerts
|

Parasitic Nematodes Exert Antimicrobial Activity and Benefit From Microbiota-Driven Support for Host Immune Regulation

Abstract: Intestinal parasitic nematodes live in intimate contact with the host microbiota. Changes in the microbiome composition during nematode infection affect immune control of the parasites and shifts in the abundance of bacterial groups have been linked to the immunoregulatory potential of nematodes. Here we asked if the small intestinal parasite Heligmosomoides polygyrus produces factors with antimicrobial activity, senses its microbial environment and if the anti-nematode immune and regulatory responses are alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
80
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(89 citation statements)
references
References 78 publications
7
80
2
Order By: Relevance
“…Our observation that axenic helminth infection results in impaired parasite fecundity is consistent with previous reports 16,17 . In addition to this reduction in fitness, we observed a non-significant, but trending decrease in worm burden in germ-free mice infected with Hpb HA107 at two weeks postinfection.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our observation that axenic helminth infection results in impaired parasite fecundity is consistent with previous reports 16,17 . In addition to this reduction in fitness, we observed a non-significant, but trending decrease in worm burden in germ-free mice infected with Hpb HA107 at two weeks postinfection.…”
Section: Discussionsupporting
confidence: 94%
“…Our description of a detailed methodology for rearing effectively germ-free Hpb larvae expands on previous work 5 and validates this model for in vivo studies. This technique will serve as an alternative to other methods of sterilizing Hpb such as antibiotic treatment of the L3 larvae prior to infection of germ-free mice 16 . Our methodology provides two improvements over such approaches.…”
Section: Discussionmentioning
confidence: 99%
“…However, reports indicate that sea lice and salmon mucus microbiota are not necessarily correlated 19 , and this supports the findings of this study where a stable, robust core microbiome was identified regardless region, center, producer practices or other factor. The factors influencing the stability of the core community are yet to be unraveled, but it is known that other parasites such as the nematode Heligmosomoides polygyrus can secrete antimicrobial compounds that shape the host-microbiota for the parasite's benefit, increasing its fitness 39 . It is known that sea lice developed a complex secretome 40 , that modulates host immune response 41 , and host mucus microbiome 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Another mechanism that helminths could use to alter the microbiota is the secretion of excretory/secretory (ES) products, which have mainly been studied in the context of immunomodulation . Recent evidence showed that these products could have a direct inhibitory effect on bacteria growth (Figure ) . Whilst most data demonstrating the ability of helminths to alter the intestinal microbiota have been acquired through studies in rodents, evidence in humans also exists indicating this is likely to occur across multiple parasitic and host species …”
Section: Helminth Infection and Metabolic Statusmentioning
confidence: 99%
“…78 Recent evidence showed that these products could have a direct inhibitory effect on bacteria growth (Figure 2). 79 Whilst most data demonstrating the ability of helminths to alter the intestinal microbiota have been acquired through studies in rodents, evidence in humans also exists indicating this is likely to occur across multiple parasitic and host species. [80][81][82] Helminth-induced alterations to microbial communities have important functional consequences for the host as demonstrated in a recent study from our own group that showed that H. polygyrus infection provides protection against asthma by modulating the intestinal microbiota to increase the availability of short-chain fatty acids (SCFA).…”
Section: Possible Contribution Of Helminthmicrobiota Interactions On mentioning
confidence: 99%